Financial integration among ASEAN+3 countries : evidence from exchange rates convergence - Lee, Chin; Mohamed, Azali (Center for Promoting Ideas (CPI), USA, 2013)
As the economies of Asian have moved towards closer economic ties in recent years, the establishment of regional exchange rate arrangement has become an important regional policy concern. A study by the Asian Development Bank forecast that Asian will be the world's largest economy by 2050. Hence, it is not reasonable for Asian to continuously depend on U.S. dollar. Asian must have its own currency and must responsible for its own financial stability. Regional cooperation (including integration) is critical for Asia’s march toward prosperity and facing vulnerabilities to global shocks. Financial integration in ASEAN+3 is assessed in this paper by examining the time-series stochastic behaviour and cointegration in a set of eight ASEAN+3 currencies. The findings imply that not all of the ASEAN+3 countries are financial integrated during the recent float. This finding provided weak support upon formation of regional monetary and exchange rate arrangement in Asia.